Sphere : a novel - Crichton, Michael, 1942-2008 (Knopf, 1987)
In the middle of the South Pacific, a thousand feet below the surface of the water, a huge vessel is discovered resting on the ocean floor. Rushed to the scene is a group of American scientists who descend together into the depths of the sea to investigate this astonishing discovery. What they find defies their imaginations and mocks their attempts at logical explanations. It is a spaceship.